2007
DOI: 10.1557/jmr.2007.0296
|View full text |Cite
|
Sign up to set email alerts
|

Thickness control of solution deposited YBCO superconducting films by use of organic polymeric additives

Abstract: We show that the thickness of yttrium-barium-copper-oxide (YBCO) superconducting films grown from trifluoroacetate precursors can be strongly modified using polymeric additives, while deposition conditions by spin or dip coating remain unchanged. A screening of different families of organic additives has been performed, and the best results have been achieved using polymers having an oxygen functionalized backbone. Two different polymeric additives, polyvinyl pyrrolidone (PVP) and poly(ethylene glycol) (PEG), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…The TGA curves confirmed the temperature difference of decomposition between pure PEG2000 and solution 30%PEG2000. The decomposition of pure PEG2000 started at 190 • C and was almost finished at 260 • C, while a significant mass loss in solution 30%PEG2000 caused by decomposition started at about 270 • C. Such a decomposition temperature difference between pure PEG and TFA-PEG samples was also observed in the study on PEG8000 addition by Morlens et al [24]. From the TGA curves in figure 9, it could be learnt that some portion of PEG2000 additive remained in the precursor film coated by solution 30%PEG2000 during the decomposition reactions, which could modify the mechanical properties and other characteristics of the precursor film.…”
Section: Thermal Analysis and Mechanical Property Measurementssupporting
confidence: 61%
See 1 more Smart Citation
“…The TGA curves confirmed the temperature difference of decomposition between pure PEG2000 and solution 30%PEG2000. The decomposition of pure PEG2000 started at 190 • C and was almost finished at 260 • C, while a significant mass loss in solution 30%PEG2000 caused by decomposition started at about 270 • C. Such a decomposition temperature difference between pure PEG and TFA-PEG samples was also observed in the study on PEG8000 addition by Morlens et al [24]. From the TGA curves in figure 9, it could be learnt that some portion of PEG2000 additive remained in the precursor film coated by solution 30%PEG2000 during the decomposition reactions, which could modify the mechanical properties and other characteristics of the precursor film.…”
Section: Thermal Analysis and Mechanical Property Measurementssupporting
confidence: 61%
“…Plasticizers were additive substances to increase the flexibility, workability or distensibility of a material [22]. Moreover, PEG additive had been used by ICMAB [23,24] and other groups [25] to enhance the viscosity of the TFA-MOD precursor solution, and thus increase the film thickness. These studies indicated that PEG was compatible with the TFA-MOD YBCO fabrication, and PEG had beneficial potential to modify the characteristics and decomposition reaction of the precursor films in pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably the reason why different ligands (TEA, DEA, PEG, etc.) are sometimes used to improve the quality of the CSD films and the use of propionic acid as solvent 16,43,52,53 . Finally, the use of propionic acid instead of TFA also helps to reduce the water absorption of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions 2 and 4 with concentrations of 0.5 M lead to an improved liquid distribution after IJP; however, they still display some coffee ring effect and so a more detailed analysis of the deposition process was required. In the case of solution 2, having a relatively low viscosity, we also analyzed the influence of including polymeric additives, such as polyethylene glycol which had previously demonstrated to be useful in increasing film thickness by spin coating . We were able to considerably increase the ink viscosity up to the maximum practical limit of the IJP nozzle (∼20 mPa s); however, huge liquid movements were detected in this case.…”
Section: Resultsmentioning
confidence: 99%